Chemometrical-electrochemical investigation for comparing inhibitory effects of quercetin and its sulfonamide derivative on human carbonic anhydrase II: Theoretical and experimental evidence - Khodarahmi, Reza (2019)
This paper reports results of a valuable study on investigation of inhibitory effects of the sulfonamide derivative of quercetin (QD) on human carbonic anhydrase II (CA-II) by electrochemical and chemometrical approaches. To achieve this goal, a glassy carbon electrode (GCE) was chosen as the sensing platform and different electrochemical techniques such as cyclic voltammetry (CV), differential pulse voltammetry (DPV), linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) were used to investigate and comparing inhibitory effects of quercetin (Q) and QD on CA-II. By the use of EQUISPEC, SPECFIT, SQUAD and REACTLAB as efficient hard-modeling algorithms, bindings of Q and QD with CA-II were investigated and the results confirmed that the QD inhibited the CA-II stronger than Q suggesting a highly relevant role of QD's-SO2NH2 group in inhibiting activity and also was confirmed by docking studies. Finally, a novel EIS technique based on interaction of Q and CA-II was developed for sensitive electroanalytical determination of CA-II and in this section of our study, the sensitivity of the developed electroanalytical methodology was improved by the modification of the GCE was with multi-walled carbon nanotubes-ionic liquid.